Identify the direct and indirect impacts of the community built environment on the health of older adults - Yang, Jinsu; Shang, Yuming; Cao, Fengxiao; Ying, Huaze; Luo, Yu (Frontiers in Public Health, 2025)
BackgroundThe global ageing population is increasing. As their physical functions deteriorate, older adults face not only physical health challenges but also mental health issues. Enhancing the health status of older adults is imperative to improve their quality of life. However, research on the health status of older adults living in the community is limited, and the association between the built environment and daily activities remains largely unexplored.ObjectiveThis study aimed to utilize structural equation modeling to (1) explore the interrelationships between the community built environment, daily activities of older adults, and their health, and (2) examine the interrelationships among their correlates.MethodsFor data collection, this study administered structured questionnaires to 494 community-dwelling older adults across ten representative urban communities in Fuzhou, China. The questionnaire comprised four validated sections: demographic characteristics, perceived community built environment features, daily activity and health outcomes. Data analysis employed structural equation modeling (SEM) using AMOS 27.0, with SPSS 27.0 for preliminary analyses, to examine both direct effects of built environment on health outcomes and indirect effects mediated through daily activities.ResultsStructural equation modeling revealed three pathways: Path 1 (community built environment →health of older adults), Path 2 (community built environment → daily exercise for older adults), and Path 3 (daily exercise for older adults →health of older adults). All three pathways were supported, indicating interaction among the factors.ConclusionThe health status of older adults is influenced by their living environment and daily activities. An improved community built environment can enhance health status among older adults. Furthermore, daily activities serve as partial mediators between community built environments and health outcomes. Our methodology and findings offer valuable insights for optimizing community built environments to promote the health of older adults.